Supervisory Implementation Authority: Strategies for Building a Professional Work Culture in Schools - Ikas Kasenda; Ahmad Zainuri; Juanidah (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The quality of education in Indonesia still faces various challenges, particularly related to teacher professionalism and the effectiveness of the learning process. The gap in teacher competency in integrating technology, implementing innovative methods, and conducting critical reflection demonstrates the need for a focused and sustainable development system. Educational supervision is a strategic instrument for improving learning quality through mentoring, evaluation, and professional development. This study aims to examine the sources of principals' authority in implementing supervision, the use of this authority, and the problems that arise in supervision practices in schools. Using qualitative methods through a literature review, this research synthesizes various theoretical concepts, empirical findings, and regulations related to educational supervision. The results indicate that principals' supervisory authority is legal-rational, derived from laws, implementing regulations, education policies, and employment contracts. Principals utilize this authority to carry out managerial functions, provide academic guidance, and conduct systematic learning evaluations. However, the implementation of supervision still faces obstacles such as time constraints, administrative burdens, lack of training, and an unsupportive work culture. This research confirms that strengthening regulations, improving principal competency, and implementing collaboration- and reflection-based supervision are crucial steps to optimize the quality of educational supervision in schools.